Opportunities and counterintuitive challenges for decentralized clinical trials to broaden participant inclusion - Goodson, Noah; Wicks, Paul; Morgan, Jayne; Hashem, Leen; Callinan, Sinéad; Reites, John (NPJ digital medicine, 2022)
Traditional clinical trials have often failed to recruit representative participant populations. Just 5% of eligible patients participate in clinical research. Participants, particularly those from minority groups, cite geographical constraints, mistrust, miscommunication, and discrimination as barriers. Here, an intersectional view of inclusion in clinical trials provides significant insights into the complex and counterintuitive challenges of trial design and participant recruitment. The US FDA have recently proposed that decentralized clinical trials (DCTs) might reduce barriers and appeal to a wider range of participants by reducing the costs and commitments required for patients to participate. While common sense and early evidence suggests that allowing participants to take part in trials at or near home has advantages in terms of convenience, travel, and perhaps even infection control, it remains to be seen if DCT approaches will yield significant improvements on participant inclusivity. Some digital studies aiming to be more inclusive on a single element of inclusion, such as race, have experienced unintended consequences in other elements, like education or gender. Implementing DCTs presents new challenges including the digital divide, the exclusion of certain tests and procedures, complexities of at-home medication delivery, and the need to build new infrastructure. We present a range of challenges and opportunities for researchers to adopt and adapt DCT approaches to create reliable evidence that applies to all of us.